Brain Tumor Infodemiology: Worldwide Online Health-Seeking Behavior Using Google Trends and Wikipedia Pageviews - Mondia, Mark Willy L.; Espiritu, Adrian I.; Jamora, Roland Dominic G. (Frontiers in Oncology, 2022)
Background: Searching the internet for information on common neurologic symptoms and diseases has been increasing in recent times. It is postulated that online search volume data could be utilized to gauge public awareness and real-world epidemiological data regarding brain tumors. Objectives: The goal of this study was to describe the pattern of online search queries of keywords related to neoplasms of the central nervous system (CNS). Methods: Using Google Trends, search activity from January 2004 – January 2021 was quantified using relative search volume (RSV). The average RSV for the first 3 years was compared with the final 3 years to account for percent change. Wikipedia article views from July 2007 – January 2021 were generated using Pageviews. Peaks in RSV and page views were then matched for related news. Results: “Brain tumor”, “brain cancer”, “glioblastoma”, and “glioma” had the highest search volume. RSV from Google Trends and views of Wikipedia pages reflected comparable data in terms of known prevalence rankings of tumor subtypes. There were no observable trends that could correlate to the rising numbers of brain tumor cases worldwide. However, headlines of personalities being diagnosed with glioblastomas were mostly responsible for temporary increases in public interest. Conclusions: Transient rises in online search volume mirror public awareness of more aggressive CNS neoplasms that have a high burden of disease. Worldwide interest in brain tumors may not necessarily correspond to clinical occurrence, but may signify an unmet gap in providing accurate online information to neuro-oncologic patients.